Implementasi Nilai-nilai Pancasila Ditengah Keberagaman Pada Lingkungan Perguruan Tinggi - Lumentia Obo, Jane Benedicta; Amalia Susanto, Titania; Ika Puspita, Ari Metalin (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study explores the implementation of Pancasila values among university students, focusing on spirituality, tolerance, mutual cooperation, and appreciation for diversity. Using a qualitative method with a case study approach data were collected through in-depth interviews, questionnaires, and observations. The findings show that students demonstrate a good understanding of Pancasila values, although challenges such as digital media influence and inconsistent character building remain obstacles. The study recommends strengthening character education, increasing social participation, and leadership training as strategic measures. Thus, Pancasila values can be effectively internalized to shape a strong young generation contributing positively to the nation.